Role of IgM and IgA Antibodies in the Neutralization of SARS-CoV-2 - Klingler, Jéromine (medRxiv, 2020)
BACKGROUND: SARS-CoV-2 has infected millions of people globally. Virus infection requires the receptor-binding domain (RBD) of the spike protein. Although studies have demonstrated anti-spike and - RBD antibodies to be protective in animal models, and convalescent plasma as a promising therapeutic option, little is known about immunoglobulin (Ig) isotypes capable of blocking infection. METHODS: We studied spike- and RBD-specific Ig isotypes in convalescent and acute plasma/sera using a multiplex bead assay. We also determined virus neutralization activities in plasma, sera, and purified Ig fractions using a VSV pseudovirus assay. RESULTS: Spike- and RBD-specific IgM, IgG1, and IgA1 were produced by all or nearly all subjects at variable levels and detected early after infection. All samples displayed neutralizing activity. Regression analyses revealed that IgM and IgG1 contributed most to neutralization, consistent with IgM and IgG fractions’ neutralization potency. IgA also exhibited neutralizing activity, but with lower potency. CONCLUSION: IgG, IgM and IgA are critical components of convalescent plasma used for COVID-19 treatment.